Unveiling the Superiority of naphthylene over biphenylene in silicon carbide 2D Architectures - Laranjeira, Jose A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Azevedo, Sérgio A.; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
In recent years, silicon carbide (SiC) has once again become a target of interest in the materials science community, this time with particular interest in two-dimensional materials, which have attracted attention due to their large surface area and infinitesimal volume. In this sense, this study introduces a novel SiC structure based on the recently reported naphthylene lattice, termed INP-SiC. It compares its electronic, mechanical and vibrational properties with the well-reported biphenylene-like SiC (BPN-SiC) via density functional theory (DFT) simulations. Both monolayers are stable at 300 K and exhibit high electron mobility, with INP-SiC reaching 94.890 102 cm2/V.s. INP-SiC also shows superior mechanical robustness, with Young's modulus (171.65 N/m) comparable to g-SiC (178.02 N/m) and T-SiC (182.22 N/m). Overall, this work is dedicated to showing the INP-SiC potential as a multifunctional 2D platform.
Keywords: 2D; Biphenylene; Naphthylene; SiC; Silicon carbide; 2d; Carbide structure; Large surface area; Material science; Science community; Structure-based; Targets of interest; Two-dimensional materials